Evaluation of direct-to-angiography suite (DTAS) and conventional clinical pathways in stroke care: a simulation study. (6th December 2021) - Bastani, Mehrad; White, Timothy G; Martinez, Gabriela; Ohara, Joseph; Sangha, Kinpritma; Gribko, Michele; Katz, Jeffrey M; Woo, Henry H; Boltyenkov, Artem T; Wang, Jason; Rula, Elizabeth; Naidich, Jason J; et al.
Abstract : Background: Rapid time to reperfusion is essential to minimize morbidity and mortality in acute ischemic stroke due to large vessel occlusion (LVO). We aimed to evaluate the workflow times when utilizing a direct-to-angiography suite (DTAS) pathway for patients with suspected stroke presenting at a comprehensive stroke center compared with a conventional CT pathway. Methods: We developed a discrete-event simulation (DES) model to evaluate DTAS workflow timelines compared with a conventional CT pathway, varying the admission NIHSS score treatment eligibility criteria. Model parameters were estimated based on 2 year observational data from our institution. Sensitivity analyses of simulation parameters were performed to assess the impact of patient volume and baseline utilization of angiography suites on workflow times utilizing DTAS. Results: Simulation modeling of stroke patients (SimStroke) demonstrated door-to-reperfusion time savings of 0.2–3.5 min (p=0.05) for a range of DTAS eligibility criteria (ie, last known well to arrival <6 hours and National Institutes of Health Stroke Scale ≥6–11), when compared with the conventional stroke care pathway. Sensitivity analyses revealed that DTAS time savings is highly dependent on baseline utilization of angiography suites. Conclusions: The results of the SimStroke model showed comparable time intervals for door-to-reperfusion for DTAS compared with a conventional stroke care pathway. However, the DTAS pathway was very sensitive to baseline angiography suite utilization, with even a 10% increase eliminating the advantages of DTAS compared with the conventional pathway. Given the minimal time savings modeled here, further investigation of implementing the DTAS pathway in clinical care is warranted.